Sectoral explanations of employment in Europe: the role of services - Antonello D'Agostino; Roberta Serafini; Melanie E. Ward (Institute for the Study of Labor (IZA), 2006)
This paper investigates the determinants of the service sector employment share in the EU-15, for the aggregate service sector, four sub-sectors and twelve service sector branches. Recently, both Europe and the US have experienced an increase in the share of service-related jobs in total employment. Although converging in all European countries, a significant gap in the share of service jobs in Europe relative to the US persists. Understanding the main factors behind this gap is key to achieving higher employment levels in Europe. This paper focuses on the role of barriers in the EU-15 which may have hindered its ability to absorb labour supply and therefore to adjust efficiently to the sectoral reallocation of labour. We find that a crucial role in this process has been played by the institutional framework affecting flexibility in the labour market and by the mismatch between workers' skills and job vacancies.
Keywords: E24; J21; J23; J24; L80; 330; services; sectoral adjustment; employment share; Europe; US; institutions in the labour and product market; Dienstleistungssektor; Beschäftigungseffekt; Institutionelle Infrastruktur; Institutioneller Wandel; EU-Staaten; USA